Causes of Aseptic Persistent Pain after Total Knee Arthroplasty - Lim, Hong-An (Clin Orthop Surg, 2017)
BACKGROUND: Persistent pain after total knee arthroplasty (TKA) is dissatisfying to the patient and frustrating to the surgeon. The purpose of this study is to evaluate the aseptic causes and clinical course of intractable pain following TKA. METHODS: Of the total 2,534 cases of primary TKA reviewed, 178 cases were classified as having aseptic persistent pain that was not resolved within 1 year after surgery. Except for the cases with periprosthetic fracture (56 knees), 122 cases of aseptic painful TKA were divided into two groups: intra-articular group (83 knees) and extra-articular group (39 knees). RESULTS: In the intra-articular group, the main reasons for pain were aseptic loosening (n = 40), polyethylene wear (n = 16), instability (n = 10), recurrent hemarthrosis (n = 5), patellar maltracking (n = 4), tendon ruptures (n = 4), and stiffness (n = 2). In the extraarticular group, 10 knees (25.6%) were found to have nerve entrapment in the spine, 6 knees (15.4%) were found to have hip osteoarthritis or femoral head avascular necrosis. The reasons for persistent knee pain in the remaining 23 knees (59.0%) still remain elusive. CONCLUSIONS: Persistent pain after TKA originated from pathology of extra-articular origin in a considerable number of cases in this study. Therefore, it is important to perform thorough preoperative evaluations to reduce pain resulting from extra-articular causes. Furthermore, meticulous surgical procedures and optimal alignment are required to reduce pain of intra-articular origin related to implant wear, instability, and patellar maltracking.